Vitellogenin and zona radiata proteins as biomarkers of endocrine disruption in peregrine falcon (Falco peregrinus) - JIMÉNEZ, B.; MORI, G.; CONCEJERO, M. A.; MERINO, R.; CASINI, S.; FOSSI, M. C. (Chemosphere, 2007)
The aim of this study was to test a specific method for the detection of Vitellogenin (Vtg) and Zona Radiata Proteins (Zrp) in plasma from peregrine falcon (Falco peregrinus) as specific biomarkers for the evaluation of the effects of endocrine disruptors. The method was assayed with different peregrine falcon individuals (including mature and immature birds of both sexes) from a Spanish population being studied in terms of their contamination with organochlorine compounds with endocrine disrupting properties. This study shows that mouse anti bird Vtg monoclonal antibody ND3C3 (Biosense) seems to be the most specific antibody in binding plasmatic lipoproteins in peregrine falcon when compared to other anti Vtg antibodies. Rabbit anti salmon Zrp polyclonal antibodies O146 (Biosense) show cross-reactivity with Zrp in the samples studied. These preliminary results confirm the applicability of both of these diagnostic tools assayed (induction of Vtg and Zrp) in detecting exposure to Endocrine Disrupting Chemicals (EDCs) in this species. The increase of Vtg and Zrp detected in male specimens suggest a potential hazard to EDCs in the peregrine falcon which represents a species still affected by organochlorine compounds, and in particular those with estrogenic activity.